MICROBIOLOGICAL ASPECTS OF THE PRODUCTION AND STORAGE OF PROCESSED CHEESE - Aslanbek B. Maremshaov; Ivan A. Evdokimov; Maria I. Shramko; Natalia N. Nikulnikova; Olga V. Lepilkina (Вестник Северо-Кавказского федерального университета, 2022)
This article contains an analysis of bacterial condition of the different types of processed cheese. Shows the necessity of the account of the component composition for pasty, ломтевых, sweet cheese, processed cheese with fillers. The regularities of influence of the composition of processed cheese on the total number of microorganisms (QMA) are in process manufacturing and storage.